Analisis Kebutuhan Kompetensi Pekerja Industri Kulit/Alas Kaki Menyongsong Era Industri 4.0 - Taukhid W Broto; Risang Pujiyanto (Epigram, 2019)
Industry 4.0 competency model has three areas of competence as salience, there is Information Systems, Computer Science, and Engineering. It hence requires adaptability to SKKNI Golongan Pokok Industri Kulit, Barang dari Kulit and Alas Kaki to accommodate these three areas as part of the competence that must be owned by industrial workers. The analysis of competency needs of leather industry and footwear industry aims to produce SKKNI accordance recommendation to the concept of industry standard 4.0. The method used is point-to-point correlation between predictors and criteria initiated by (Bartram, 2005) and further developed by (Prifti, Knigge, Kienegger, & Krcmar, 2017). In the end SKKNI which is embraced through the application of this recommendation will be use as reference for the formal and non-formal curriculum education improvement to prepare industry workforce towards industry 4.0 era.